'I have more control over my life': A qualitative exploration of challenges, opportunities, and support needs among autistic university students. (May 2021) - Scott, Matthew; Sedgewick, Felicity
Background: Autistic people are known to experience more mental health issues than non-autistic people, and the same is true among university students. These difficulties can have long-term consequences, such as dropping out of university and unemployment. Understanding the challenges autistic students face can help institutions to better support this group, while allowing celebration of the opportunities higher education offers. Methods: 12 autistic university students took part in semi-structured interviews about their mental health, the impact of university on their mental health, and their experiences of support while in higher education. Interviews were subject to thematic analysis. Results: Three key themes were identified from autistic student accounts: Relationships, Independence, and Support. While each of these encompassed positive and negative elements, Relationships were described as tying everything together – when these were supportive, things went well, but when they were characterized by stigmatizing attitudes, students experienced much greater difficulties at university. Conclusions: Autistic students can and do thrive at university, as shown by many of our participants. However, all faced significant challenges with their mental health at times, and experienced varying levels of support. Improving autism knowledge among staff, with emphasis on enabling better relationships, would make a significant difference to the autistic student experience.